Rain-generated overland flow as a factor in the development of some stratified slope deposits: A case study from the Pays du Buëch (Préalpes, France) - van Steijn, Henk; Hétu, Bernard (Géographie physique et Quaternaire, 1997)
AbstractA large exposure of stratified slope deposits, and a partly vegetated active talus, both situated near Veynes (Préalpes du Sud, France) were studied. On the active slope, dry grain flows, erosion by rain-generated overland flow, and 'aggregate' flows caused by high-intensity rainstorms are most typical. The term 'aggregate' flow was chosen because of the abundant presence of silty aggregates (diameter 0.5-3 mm) within these deposits which closely resemble small debris flows. These three processes operate in a fixed sequence thus producing a characteristic stratification pattern. Forms and sediments caused by the processes mentioned are described in detail. Subsequently, the results are applied in the interpretation of the sections of the relict deposits. The correlation and the interpretation problems with regard to processes involved between deposits on the active slope and within the relict sediment mass are discussed, together with the traces of other processes recognised within the latter. The results are placed in a wider context of stratified slope deposits and their palaeoclimatic significance.